A Pilot Evaluation of an Art Therapy Program for Refugee Youth From Burma. Issue 1 (2nd January 2016) - Kowitt, Sarah Dorothy; Emmerling, Dane; Gavarkavich, Diane; Mershon, Claire-Helene; Linton, Kristin; Rubesin, Hillary; Agnew-Brune, Christine; Eng, Eugenia
Abstract: Art therapy is a promising form of therapy to address mental health concerns for refugee youth. This article describes the development and implementation of a pilot evaluation of an art therapy program for refugee adolescents from Burma currently living in the United States. Evaluation activities were based on the Centers for Disease Control and Prevention's evaluation framework and implemented through a partnership of art therapists and public health researchers in North Carolina. Findings indicate that evaluation activities were feasible, acceptable, and provided baseline measures of mental health for the adolescents sampled. Through a discussion of evaluation components and results, this pilot evaluation offers an example of how art therapy organizations can integrate program evaluation using existing evaluation frameworks, while engaging stakeholders and building organizational capacity.